2021
DOI: 10.3389/feduc.2021.675329
|View full text |Cite
|
Sign up to set email alerts
|

Zines as Reflective Evaluation Within Interdisciplinary Learning Programmes

Abstract: This paper presents a unique method for documenting and reflecting learning in interdisciplinary science learning settings, which prioritises the perspectives of marginalised learners and which may be used across cultural contexts. Short for “magazine” or “fanzine,” zines are small DIY booklets which can contain poetry, narrative, drawings, comics, collage and more. Often associated with radical or alternative cultures, they can become a kind of self-made soapbox for the creator, a material artifact that, by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…By traversing rational-intuitive distinctions, boundaries can be transgressed and the research produced can be unique and richly detailed (in a different way from the detail provided by written modes of communication). Aligned with this, Brown et al, (2021) found that by creating 'zines' -as both text and visual-based media -young learners expressed personalized reflections on educational experiences in new and liberating ways, as the makers of the zines became the creators and the 'expert' on their experience. Leary et al (2014: 230) note that the freedom of such creative methodologies does bring a degree of risk as the role of the researcher changes; also through the creation of art the researchers effectively put their 'personality on the line'.…”
Section: Exploring the Reflective Potential Of Arts-based Approachesmentioning
confidence: 86%
“…By traversing rational-intuitive distinctions, boundaries can be transgressed and the research produced can be unique and richly detailed (in a different way from the detail provided by written modes of communication). Aligned with this, Brown et al, (2021) found that by creating 'zines' -as both text and visual-based media -young learners expressed personalized reflections on educational experiences in new and liberating ways, as the makers of the zines became the creators and the 'expert' on their experience. Leary et al (2014: 230) note that the freedom of such creative methodologies does bring a degree of risk as the role of the researcher changes; also through the creation of art the researchers effectively put their 'personality on the line'.…”
Section: Exploring the Reflective Potential Of Arts-based Approachesmentioning
confidence: 86%
“…However, the majority of researchers connect the penetration of zines into mass culture with the spread of a large number of small newspapers and magazines, which became widespread in the 1930s. Dissatisfaction with the official press and lack of diversity, the desire to express own opinion, to tell their story, led to the fact that American fans of science fiction, often through social club, began to publish «magazines for fans» or «fan-zines» to share science fiction stories and communicate with public (Brown, Hurley, 2021). Thus, the zine was created as an oppositional and marginal publication within a certain community and became a great way to establish new relationships with like-minded individuals.…”
Section: Iсторiяmentioning
confidence: 99%
“…Other types of scholarship are also absent from most databases, including, e.g., choreographies, musical compositions, zines, blogs, datasets, and software. Some works are “small circulation ephemera” (e.g., zines as described by Brown et al, 2021 ), and archiving and cataloging these works may be antithetical to the ethos in which they were created. In other cases, ephemera are cataloged and preserved (e.g., Esling, 2013 ), but those archives are not widely used in academic evaluation.…”
Section: What Becomes a Bibliometric Artifact?mentioning
confidence: 99%